Edukasi dan Screening Kesehatan sebagai Upaya Pencegahan Anemia pada Remaja Perempuan di MTs Nurul Falah Areman, Depok - Agustiyawan; Chandrayani Simanjorang; Rabia; Andi Sirada; Ismaya Ramadhanti; Asti Elysia Rahmatul Fitri; Anggrahita Dwi Ariantini (Warta LPM, 2024)
Adolescent girls are a vulnerable group who can experience anemia due to low consumption and absorption of iron, blood loss during menstruation, and increased iron requirements. Anemia can cause impaired growth and health status as well as decreasing academic performance and cognitive development. Education regarding nutrition and screening for adolescent girls is an appropriate, effective, and sustainable method for preventing anemia due to iron deficiency. Therefore, in this community service activity, a combination of education and screening is carried out to prevent the development of anemia in adolescent girls at MTs Nurul Falah Areman. The community service was carried out using the lecture method and filling out a questionnaire in the form of a pretest and post-test to assess the increase in knowledge consisting of 20 multiple choice questions. The result obtained from 53 students showed that 52,8% had good knowledge regarding anemia and 47,2% had poor knowledge. Based on an examination of Hb levels, 25% of adolescent girls fall into the category of moderate and mild anemia. Education regarding anemia should be carried out routinely at MTs Nurul Falah Areman. Furthermore, MTs Nurul Falah Areman can be a target for blood supplement tablets from the nearest Community Health Center, so that in the future no more young women will be found suffering from anemia.